2018
DOI: 10.1088/1361-6595/aabab6
|View full text |Cite
|
Sign up to set email alerts
|

A rotational Raman study under non-thermal conditions in a pulsed CO2glow discharge

Abstract: A rotational Raman study under non-thermal conditions in a pulsed CO 2 glow discharge. Plasma Sources Science and Technology, 27(4), [045009].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…These measurements were performed with the short discharge tube (23 cm), which fits into the sample compartment of the FTIR; however, the atomic oxygen measurements were made in the long discharge reactor (67 cm). The radii of both tubes are the same, and there is no axial gradient along the tube since the diffusion dominates over the motion due to the gas flow, homogenizing the concentrations as has been confirmed by Raman scattering measurement along the tube axis [57]. Therefore, the main difference between the two discharge tubes is the length between the electrodes, which, for a given flow, implies a different residence time (τ res ) of the gas in the plasma.…”
Section: Co 2 Dissociation and O Atom Densities 51 Dissociation Fraction In Continuous Co 2 Plasmamentioning
confidence: 74%
“…These measurements were performed with the short discharge tube (23 cm), which fits into the sample compartment of the FTIR; however, the atomic oxygen measurements were made in the long discharge reactor (67 cm). The radii of both tubes are the same, and there is no axial gradient along the tube since the diffusion dominates over the motion due to the gas flow, homogenizing the concentrations as has been confirmed by Raman scattering measurement along the tube axis [57]. Therefore, the main difference between the two discharge tubes is the length between the electrodes, which, for a given flow, implies a different residence time (τ res ) of the gas in the plasma.…”
Section: Co 2 Dissociation and O Atom Densities 51 Dissociation Fraction In Continuous Co 2 Plasmamentioning
confidence: 74%
“…In the past decade, many papers, both experimental (e.g., Silva et al, 2014Silva et al, , 2017Klarenaar et al, 2017Klarenaar et al, , 2018Klarenaar et al, , 2019Stewig et al, 2020;Terraz et al, 2020;van den Bekerom et al, 2020) and computational (e.g., Bogaerts, 2014, 2015;Pietanza et al, 2015Pietanza et al, , 2017aPietanza et al, ,b, 2018aPietanza et al, ,b, 2020Bogaerts, 2016, 2018;Capitelli et al, 2017, Heijkers andGrofulović et al, 2018;Silva et al, 2018;Bogaerts, 2018, 2019;Kotov and Koelman, 2019;Terraz et al, 2020), focused on the role of the vibrational kinetics in plasmas, but mainly at low pressure conditions (few mbar up to a few hundred mbar). Most of these studies revealed the importance of the vibrational kinetics at specific conditions (low gas temperature, low pressure) and their contribution to a high energy efficiency.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
“…For all these setups, a triple grating spectrometer is the most common method to eliminate the stray light, [ 11,13,20 ] but such a method requires a complicated optical setup. A volume Bragg notch filter with single grating can also be used to get rid of Rayleigh scattering signal, [ 19,21 ] but the alignment of the optical path is difficult to achieve. Recently, a new setup has been developed by Chen et al [ 22 ] for middle‐pressure discharges, which is implemented in low‐pressure discharges.…”
Section: Introductionmentioning
confidence: 99%